Dikmas Lantas Unit Dikyasa dalam Menekan Angka Kecelakaan Lalu Lintas - Adam Rizki Satya Nugraha (Advances in Police Science Research Journal, 2021)
In our daily life, we cannot escape from those whose names are alat transportation passing through raya roads from places to places to other places. View densate traffic then from there government feel need need need necessary to issue disciplinary laws. One of the tasks for members Polri is to provide services to the community by taking measures to preventive measures against things that can trigger disruption of security and order in society. One of the precautionary measures taken was the guidance and counseling to the community in the field Then Traffic. Therefore, this study aims to find out the details of the implementation of community service activities and units of the Bekasi City Metro Police and analyze the effectiveness of the Dikmas Thenas activity mechanism of the Dikyasa unit of the Bekasi Metro Police. This research is a descriptive study using a qualitative approach. In focus research, writers determine disciplinary discrimination discipline in emphasize decrease outrage invactiveness in law zone Polres Metro City Bekasi. Data obtained through interviews, observation, and documentation. The data that has been obtained were analyzed through several stages, namely data reduction, data presentation, and drawing conclusions. The results showed that the implementation of Dikmaslantas activities at the Bekasi City Police was running smoothly. members who have enough, good supervision enough budget. But in pandemic virus in now , still effective because must maintain distance one nother and reduce he peace to break tali chains corona virus distribution.Implementation Previously effective, but now is less effective due to barriers by inhibiting factors such as factors, conditions, and conditions in a city, a pandemicmic zones.